Implementasi Smart Digital Interactive Laboratory Berbasis Augmented Reality dalam Penguatan Literasi Sosiosaintifik Siswa - Kartyka Nababan; Dina Mariana Siregar; Victor Tarigan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The Fourth Industrial Revolution and Society 5.0 are driving the transformation of science education towards the development of 21st-century competencies, including socioscientific skills. However, the abstraction of concepts and limitations in representing complex phenomena pose challenges in chemistry learning. Immersive technologies such as Augmented Reality (AR) and Artificial Intelligence (AI) offer solutions through the creation of interactive and personalized learning environments. This study aims to: (1) implement AR and AI-based Smart Digital Laboratory (Smart-DIL) media on environmental pollution material; (2) analyse its impact on student engagement and enthusiasm for learning; and (3) explore the development of environmental awareness and socioscientific skills through an eco-enzyme project. This qualitative research with an instrumental case study design involved 22 students from class XI IPA SMA Kristen Sonder who were selected purposively. Data collection was carried out through participant observation, in-depth interviews, questionnaires, and documentation studies. The data was analysed interactively following the Miles, Huberman, and Saldana model. The implementation of Smart-DIL created a dynamic and immersive learning environment. A significant increase in engagement and enthusiasm for learning was observed, as demonstrated by intensive interaction with AR objects and critical discussions. This application also acts as a catalyst in fostering environmental awareness and socio-scientific skills, which are manifested in the full engagement of students during the practice of making eco-enzymes. The AR and AI-based Smart Digital Laboratory is effective in transforming chemistry learning into contextual and competency-based learning. The integration of this technology in the Merdeka Curriculum not only increases learning engagement but also fosters students' socio-scientific skills and digital literacy.